2016
DOI: 10.15740/has/irjaes/7.1/56-62
|View full text |Cite
|
Sign up to set email alerts
|

Economic analysis of pandal (structure for creeper crops) vegetables cultivation in Coimbatore district of Tamil Nadu

Abstract: In India about 50 per cent of the population depends on agriculture, majority are small land holding farmers.As per world agriculture statistics (FAO, 2010). India is the world's largest producer of many fresh fruits and vegetables with a large and diverse agricultural sector in the world next to China. As of now, India ranks second worldwide in farm output. Agriculture with allied sectors contributed 13.7 per cent of the GDP during 2010-11 (CSO, 2011). This research paper aims to study the cost and returns of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
2
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 1 publication
3
2
0
Order By: Relevance
“…61,537/-in farmers practice method this is calculated by making average of the two year results. Balaji et al, 2016 had also reported the similar results in a study taken up in three blocks and 3 villages in each block in Tamil Nadu. Two year average of BC ratios was 2.82:1 and 3.95:1 in farmer's practice and on-farm trial respectively.…”
Section: Average Of Two Year (2016 And2017) Kharif Season Resultssupporting
confidence: 69%
See 1 more Smart Citation
“…61,537/-in farmers practice method this is calculated by making average of the two year results. Balaji et al, 2016 had also reported the similar results in a study taken up in three blocks and 3 villages in each block in Tamil Nadu. Two year average of BC ratios was 2.82:1 and 3.95:1 in farmer's practice and on-farm trial respectively.…”
Section: Average Of Two Year (2016 And2017) Kharif Season Resultssupporting
confidence: 69%
“…Peter et al, (2008) reported that cucurbit vegetables such as bitter gourd, snake gourd, ridge gourd, and ivy gourd grown on pandal system produced higher yields and better fruit quality in Kerala. Balaji et al, (2016) in their study reported that ribbed gourd cultivated on pandal system in 3 villages each of Anaimalai block and Madukkarai block has given an average yield of 17.50 tonnes with net returns of Rs.145285 per hectare which was technologically improved practice over traditional method of ribbed gourd cultivation in Tamilnadu.…”
mentioning
confidence: 99%
“…The cost of human labour was observed highest among all expenditures because picking/harvesting and inter-culture operations were done manually. The findings were in consonance with Balaji et al (2016); Rathod et al (2016) and Singla et al (2006). It could be also inferred from Shende et al (2015) and Rathod et al (2016).…”
Section: Cost Conceptssupporting
confidence: 83%
“…The identical results were also reported by Hile et al (2012). The BCR results for bitter gourd reported by Balaji et al (2016) were closer to these findings. The results of overall input-output ratio on the basis of Cost C 2 was in conformity with Daundkar et al (2015), Shende et al (2015) and Krishna and Chandra (2017).…”
Section: Input-output Ratio Over Different Costssupporting
confidence: 76%
See 1 more Smart Citation